2016
DOI: 10.1038/srep36960
|View full text |Cite
|
Sign up to set email alerts
|

Lineage diversification, homo- and heterologous reassortment and recombination shape the evolution of chicken orthoreoviruses

Abstract: The near complete genome sequences of ten field avian orthoreovirus (ARV) strains collected from young chicken between 2002 and 2011 in Hungary have been determined in order to explore the genetic diversity and evolutionary mechanisms affecting ARVs in this region. Sequence analyses and phylogenetic calculations revealed similar geographic distribution and distinct evolution in case of eight studied strains that were closely related to the recently described Hungarian strain T1781. The remaining two strains sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…RNA recombination usually occurs between regions of high sequence similarity. Such homologous recombination between cognate genome segments has been noted in ARVs, where as many as twelve recombination events between multiple cognate genome segments of different circulating virus strains have been predicted [ 62 ]. However, non-homologous recombination can also occur, with genetic exchange taking place between different virus genomes [ 63 ] or, more rarely, between viral and cellular RNA [ 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA recombination usually occurs between regions of high sequence similarity. Such homologous recombination between cognate genome segments has been noted in ARVs, where as many as twelve recombination events between multiple cognate genome segments of different circulating virus strains have been predicted [ 62 ]. However, non-homologous recombination can also occur, with genetic exchange taking place between different virus genomes [ 63 ] or, more rarely, between viral and cellular RNA [ 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since the three viruses are paraphyletic when comparing other homologous proteins ( Figure 1 A), lateral gene transfer via genome segment reassortment between these evolving virus species presumably occurred after the p16 recombination event. Recombination events and genome segment reassortment are well-linked to intra-species ARV evolution, with some suggestion that similar inter-species genetic events may have occurred between orthoreovirus species [ 62 ], possibly early post-speciation.…”
Section: Resultsmentioning
confidence: 99%
“…This is indicated by detections of reassortment and intragenic recombination in eight, respectively seven, of nine LEAV strains. This is all the more clear for orbiviruses with great antigenic diversity like BTV [57,66,67] and AHSV [68], but also for orthoreoviruses [69][70][71] and rotaviruses [72].…”
Section: Discussionmentioning
confidence: 99%
“…The nt BLAST of the 11 ARV isolates revealed that they share high nt identities (>95%) with strains identified in Hungary, France, and Brazil. Initially, 4599-V-04A was isolated from broiler flocks in Hungary (2004), and field isolates were also acquired from flocks in France and Brazil during the past 5 y ( Troxler et al., 2013 , Farkas et al., 2016 ). However, field strains in genotype II shared high similarity with LN160607-1, which was initially reported in China ( Zhang, et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the genetic characterization of σC protein, ARV isolates are divided into multiple genotypes ( Kant et al., 2003 , Day, 2009 , Goldenberg et al., 2010 ). Recent studies also have shown that all ARV isolates are divided into 4 to 6 clusters ( Dandar et al., 2013 , Lu et al., 2015 , Farkas et al., 2016 , Tang et al., 2016 , Noh et al., 2018 ).…”
Section: Introductionmentioning
confidence: 98%